The Results of Diagnostic Laparoscopy Examinations - An 8 - Years Experience - Arıkan, İlker and Barut, Aykut and Harma, Müge and Harma, Mehmet İbrahim and Gezer, Şener (Gynecology Obstetrics & Reproductive Medicine, 2011)
OBJECTIVE: The aim of this study was to evaluate the results of diagnostic laparoscopy examinations performed in our clinic. STUDY DESIGN: Hospital records of 93 patients, who had undergone diagnostic laparoscopy in our clinic between June 2001 and December 2008, were evaluated retrospectively. RESULTS: The most common indications for diagnostic laparoscopy were infertility (n=81, 87.1%) and chronic pelvic pain (n=12, 12.9%). Pelvic findings were noted in 33.3% (27/81) of infertile patients and 58.3% (7/12) of patients with chronic pelvic pain. The frequencies of endometriosis and adhesions were 16.1% (n=15) and 9.6% (n=9), respectively, among all cases. CONCLUSION: Diagnostic laparoscopy, used as the standard method for the assessment of patients with infertility and chronic pelvic pain, should be used more often in differential diagnosis. Inclusion of diagnostic laparoscopy in residency training programs would reduce the complication rates in future clinical practice.